1998
DOI: 10.1136/hrt.80.3.276
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and morphological characteristics in Streptococcus bovis endocarditis: a comparison with other causative microorganisms in 177 cases

Abstract: Conclusions-S bovis endocarditis is a severe illness because of the more common involvement of multiple valves, and of the frequent occurrence of haemodynamically relevant valvar regurgitation and infectious myocardial infiltration. (Heart 1998;80:276-280)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
68
2
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(79 citation statements)
references
References 35 publications
8
68
2
1
Order By: Relevance
“…Recently published studies either have not addressed the diversity of S. bovis isolates in the context of S. bovis endocarditis (4,12,14) or have addressed this issue in a preliminary and often contradictory fashion (2,3). Prior to the description of S. gallolyticus, Ruoff et al reported that among S. bovis biotypes identified by the API Rapid Strep system (Analytab Products, Plainview, N.Y.) and cellular fatty acid content, biotype I was more likely than biotype II to be associated with both endocarditis and malignant or premalignant colonic lesions (15).…”
mentioning
confidence: 99%
“…Recently published studies either have not addressed the diversity of S. bovis isolates in the context of S. bovis endocarditis (4,12,14) or have addressed this issue in a preliminary and often contradictory fashion (2,3). Prior to the description of S. gallolyticus, Ruoff et al reported that among S. bovis biotypes identified by the API Rapid Strep system (Analytab Products, Plainview, N.Y.) and cellular fatty acid content, biotype I was more likely than biotype II to be associated with both endocarditis and malignant or premalignant colonic lesions (15).…”
mentioning
confidence: 99%
“…bovis, a nonenterococcal lancefield group D streptococcus, is a transient colonic commensal with fecal carriage rate of 5 -13 % in healthy adults (Potter et al, 1998;Dubrow et al, 1991), and accounts for 11-12% of infective endocarditis (Ballet et al, 1995;Kupferwasser et al, 1998). Traditionally, S. bovis has been classified into three distinct biotypes; I, II/1, and II/2, www.intechopen.com based on phenotypical and genetic characteristics (Coykendall & Gustafson, 1985).…”
Section: Streptococcus Bovismentioning
confidence: 99%
“…Ниже представлена этиология современного ИЭ в соответствии с частотой выявления основ-ного возбудителя [8]:…”
unclassified